2018
DOI: 10.1161/hypertensionaha.118.11558
|View full text |Cite
|
Sign up to set email alerts
|

Improving Hypertension Control in Primary Care With the Measure Accurately, Act Rapidly, and Partner With Patients Protocol

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
60
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(61 citation statements)
references
References 27 publications
0
60
0
1
Order By: Relevance
“…The main cause of false TI was physicians’ concerns about the BP measured in the clinic being inaccurate, which is consistent with the reports of previous studies. 8 , 9 HT treatment should be designed as a framework for physicians to improve the outcome of HT care and reduce TI. 9 However, appropriated TI should be more accurate if patients are encouraged to use SMBP at home, as the present study revealed that this is the second greatest cause of false TI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main cause of false TI was physicians’ concerns about the BP measured in the clinic being inaccurate, which is consistent with the reports of previous studies. 8 , 9 HT treatment should be designed as a framework for physicians to improve the outcome of HT care and reduce TI. 9 However, appropriated TI should be more accurate if patients are encouraged to use SMBP at home, as the present study revealed that this is the second greatest cause of false TI.…”
Section: Discussionmentioning
confidence: 99%
“… 8 , 9 HT treatment should be designed as a framework for physicians to improve the outcome of HT care and reduce TI. 9 However, appropriated TI should be more accurate if patients are encouraged to use SMBP at home, as the present study revealed that this is the second greatest cause of false TI. Furthermore, current clinical guidelines indicate that SMBP is effective in lowering BP.…”
Section: Discussionmentioning
confidence: 99%
“…Variations in screening standards and policies have led to many patients who attend health facilities not having their blood pressure measured, many who have it measured not having it measured correctly, and many who have elevated readings not being diagnosed or treated for hypertension . Therapeutic inertia (not initiating or intensifying treatment despite elevated blood pressure) is a recognized problem, but diagnostic inertia is another, largely unrecognized, problem. Requiring ambulatory blood pressure monitoring is an additional potential cause of diagnostic inertia.…”
Section: Lessons Learnedmentioning
confidence: 99%
“…The few studies that report on such operational changes tend to be small (single setting) or lack the details necessary to be usable by and transferable to other primary care practices. [12][13][14][15] Even when operational changes are known, implementing them in busy primary care practices can be difficult. External support, such as providing practices with a facilitator to help foster change, is effective.…”
Section: Introductionmentioning
confidence: 99%